New Method for Measuring the Polarity and the Selectivity of the Capillary Gas Chromatography Columns - M. Abdel-Aziz, Hasan; M. Zourb, Mohd; Taylor, D. (Asian Journal of Chemistry, 2010)
An alternative method to McReynolds' method is introduced in this work to measure the column's polarity and selectivity. McReynolds' method was developed primarily for measuring the polarity of packed columns, so it suffers from inaccuracy in measuring the polarity of capillary columns, especially those with a high phase ratio. The new method utilizes the plot of logarithm of adjusted retention times for different homologous series versus the number of carbons in each member multiplied by a hundred. The intercept of the alkane (RH) used as a reference was subtracted from the other series intercepts (RX1, RX2,...). The sum of differences divided by the mean value of slopes of each series predicts the calculated overall polarity. Selectivity, from the other side, was related to the ratio of each individual intercept divided bylhe mean value of the slope as shown in eqn. (4). The correlation between the new method and McReynolds' either in polarity or selectivity measurements indicates that there is a high correlation in all cases less than 1% significant error.